Mitigasi Bencana Alam Tanah Longsor Pada Nungnung Waterfall Desa Pelaga Kecamatan Petang Kabupaten Badung - Agnes Ayu Biomi; I Gusti Agung Haryawan; Komang Angga Prihastini; Ni Luh Gede Maytadewi Negara; Made Adhyatma Prawira Natha Kusuma; Ni Putu Eny Sulistyawati (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Pelaga Village is one of the villages in Badung Regency, Petang District which is a tourist village with one of the tours being the Nungnung Waterfall. Pelaga Village is one of the areas designated by the Badung Regency BPBD as a landslide-prone area. This is also supported by data obtained from the population census of Pelaga Village, Banjar Nunnung. Therefore, landslide disaster mitigation is for the community. The method used is socialization and simulation. The socialization was carried out with the aim of providing understanding and knowledge related to earthquakes and landslides to the community. The results obtained, public knowledge has increased, judging from the results of the pre-test and post-test given. Followed by a simulation followed by several stakeholders including BPBD, PRB Forum, local residents, tour guides, seka truna - truni (youth - young people) Banjar Nungnung, Bendesa Adat (Kepala Adat) Banjar Nungnung, and KKN - PPM University students Bali International . The results obtained, the community is more related to disaster preparedness, especially in terms of vigilance and preparedness if a landslide disaster is based on direct action. keywords: landslides, disaster mitigation, Nungnung Waterfall